Memberdayakan Keterampilan Berpikir Kritis dengan Model Pembelajaran Remap TmPS (Reading Concept Map Timed Pair Share) - Fatia Rosyida; Siti Zubaidah; Susriyati Mahanal (Universitas Sebelas Maret, 2016)
Critical thinking skills are less empowered in learning. Critical thinking skills can be empowered through cooperative learning. One of learning model combined with cooperative, and can potentially empower critical thinking skills are Remap TmPS (Reading Concept Map Timed Pair Share). The purpose of this study was to determined the effect of Reading-Concept Map Timed Pair Share (Remap TmPS) learning to the critical thinking skills. The research is a quasi experimental research with Nonequivalent Pretest-Posttest Control Group Design. The research sample is X MIA 2 class and X MIA 3 of SMAN 2 Batu. Data obtained from the critical thinking skills that are scored with the essay test rubric critical thinking skills integrated essay test. This data analyzed using anacova test. The results showed Remap TmPS effect on students' critical thinking skills, bercause as each stage of learning gives students the opportunity to practice the skills of critical thinking.Keywords: critical thingking skills, Remap-TmPS